Legal Regulation And Content Of Law Application And LawEnforcement Functions Within Penitentiary Bodies AndInstitutions - Stepaniuk, Anatolii; Filipenko, Nataliia; Salaievayna, Karyna; Lukashevych, Serhii (Archives of Criminology and Forensic Sciences, 2024)
This article demonstrates that current legislation provides grounds to classify penitentiary bodies and institutions (bodies and institutions for the enforcement of punishments) as law enforcement agencies. The activities of bodies and institutions for the enforcement of punishments, which are organizationally part of the State Criminal-Executive Service of Ukraine, are viewed as law enforcement activities. This is because the organizational structures and officials of these bodies perform law application and law enforcement functions. The law application and law enforcement functions of penitentiary bodies and institutions are carried out in the area of punishment enforcement. Understanding the content of these functions is possible by clarifying activity areas and main tasks of penitentiary bodies and institutions, as defined in the laws and regulations governing their activities